Hyperspace : a scientific odyssey through parallel universes, time warps, and the 10th dimension - Kaku, Michio (New York : Oxford University Press, 1994)
Discusses why physicists think that universes are parrallel, plural, and full of wormholes.
Includes bibliographical references and index.
Library Journal.
Publisher's Weekly.
Wilson's Public Library.
Adult
Keywords: Hyperspace; Kaluza-Klein theories; Superstring theories; Hyperspace; Kaluza -- Klein theories; Superstring theories